Rapid COVID-19 Antigen Testing in Croatia: Risk Perception Plays an Important Role in the Epidemic Control - Primorac, Dragan; Perić, Vitorio; Matišić, Vid; Molnar, Vilim; Zadro, Renata; Vince, Adriana; Lauc, Gordan; Polašek, Ozren (Frontiers in Public Health, 2021)
Aim. To explore the clinical presentation and epidemiological history in the subjects who underwent SARS-CoV-2 antigen testing. Methods. We included 1000 consecutive subjects who presented themselves at the diagnostic clinic in Croatia, and analysed their symptoms and epidemiological history. All subjects were classified in three groups, according to their reason of arrival; symptomatic, contacts of confirmed patients and those who were tested due to administrative reasons. Results. On average, there were 24% of positive antigen results; the positivity rate was 51% among symptomatic, 16% in contacts and 5% of administrative patients. The commonest symptoms of the disease include febrility and anosmia. We developed a clinical score to predict SARS-CoV-2 positivity, which had area under curve of 79.3 [95% CI 75.8-82.8]. Contact with isolated person (odds ratio 0.54 [95% confidence intervals 0.31-0.94]) and international travel had protective effect (0.20 [0.09-0.43]), suggesting that risk perception and mandatory pre-travel measures had a key role in the determination of the infection risk. Conclusions. Combination of clinical symptoms can have reasonable predictive power for SARS-CoV-2 infection. Risk perception seems to have a role in the epidemic spread, probably via stricter adherence to personal preventative measures.